Applied General Equilibrium An Introduction - Cardenete, Manuel Alejandro; Guerra, Ana-Isabel.; Sancho, Ferran; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This advanced textbook aims at providing a simple but fully operational introduction to applied general equilibrium. General equilibrium is the backbone of modern economic analysis and as such generation after generation of economics students are introduced to it. As an analytical tool in economics, general equilibrium provides one of the most complete views of an economy since it incorporates all economic agents (households, firms, government, foreign sector) in an integrated way that is compatible with microtheory and microdata. The integration of theory and data handling is required for successful modeling but it requires a double ability that is not found in standard books. With this book we aim at filling the gap and provide advanced students with the required tools, from the building of consistent and applicable general equilibrium models to the interpretation of the results that ensue from the adoption of policies. The topics include: model design, model development, computer code examples, calibration and data adjustments, practical policy examples.
Foreword -- 1 Introduction -- 2 An Overview of General Equilibrium Theory -- 3 A simple General Equilibrium Model -- 4 A General Equilibrium Model with a Government Sector -- 5 Further Extension of the Model: External Sector, Labor Market and Consumption Technology -- 6 Data Base and Model Calibration -- 7 Real-World Examples of Applied General Equilibrium Analysis -- Index.
Keywords: Economics; Economic policy; Microeconomics; Economics/Management Science; Economic Theory; Microeconomics; Economic Systems; Economic Policy